Understanding the Objectives of Pigs Farming Development in Arfak Tribe Farmers, West Papua - Deny A. Iyai; Bernadin Gobay; Alexander Yaku (Hasanuddin University, 2015)
The multifunction of pigs for the Papuan are divergences and interelated. This study was aimed to seek the objectives of keeping pigs by Arfak tribe and to find the trend relationships of economical and socio-cultural components determining the development of pig farming systems in Manokwari. A one-month field research was done at Manokwari Barat district. Quiztionaire was the tool used to record and collect the data. Snowball method was applied to chose the pig farmer participants and 60 respondents were participated. Several variables were quantified to measure the percentages of socio-cultural and economicalobjectives. The finding shown that income generation, savings barter were the subsequent components shaping the economic objectives and while organic fertilizer and biofertilizer resulted from manure were not applied yet. Although dung was frequently produced and spreaded at the pig house and around backyard. Socio-culture was done in the means of merrital prices, peaceness, gift and parties, respectively. The other findings were that the alternation of pig development indicated by herd size had positive relationship with the two motives. Similar relationship was shown by number of aided farmers. Hence, the changes of pig farming systems, e.g. extensive to semi-intensive and/or intensive to semi-intensive had shown weak relationship.